Anticancer activity of essential oils: a review. (26th July 2013) - Bhalla, Yashika; Gupta, Vinay Kumar; Jaitak, Vikas
Abstract: Natural essential oil constituents play an important role in cancer prevention and treatment. Essential oil constituents from aromatic herbs and dietary plants include monoterpenes, sesquiterpenes, oxygenated monoterpenes, oxygenated sesquiterpenes and phenolics among others. Various mechanisms such antioxidant, antimutagenic and antiproliferative, enhancement of immune function and surveillance, enzyme induction and enhancing detoxification, modulation of multidrug resistance and synergistic mechanism of volatile constituents are responsible for their chemopreventive properties. This review covers the most recent literature to summarize structural categories and molecular anticancer mechanisms of constituents from aromatic herbs and dietary plants. © 2013 Society of Chemical Industry